Enacting an emergency EFL course in an Indonesian disadvantaged condition - Khotimah, Khusnul; Apgrianto, Kurniawan; Mustofa, Mutmainnah; Ubaidillah, M. Faruq; Amalia, Shinta (JEES (Journal of English Educators Society), 2021)
Situated in a disadvantaged condition in Lombok, Indonesia, the present study looks at the enactment of an emergency EFL course after earthquake and aftershock circumstances in a public university in the region. For such a purpose, forty-two non-English department students who attended the course in four face-to-face and nine asynchronous meetings were recruited using a convenience sampling technique. A set of questionnaire was disseminated to document participants’ responses on the course implementation. Observation and semi-structured interviews were also conducted to portray the pedagogical praxis. The findings suggest that the course delivery did not utterly reflect an effective teaching-learning process accordingly due to various factors. Barriers to using the WhatsApp tool also existed. Interestingly, the students positively reflected the course as the best way to learn in a disadvantaged condition. However, they were not confident with their attainment in English skills and components. Further considerations on how to design materials and assessment instruments and build a decent interaction are needed in learning under such disadvantaged condition. HIGHLIGHTS : The findings evince that the course delivery did not utterly reflect an effective teaching-learning process accordingly due to various factors. Barriers to using the WhatsApp tool also existed. The students positively reflected the course as the best way to learn in an emergency learning milieu. The teacher appeared to be able to maintain students’ motivation. Further considerations on how to design materials and assessment instruments and build a decent interaction are needed in learning under such disadvantaged conditions.